2018
DOI: 10.1002/ana.25334
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amyloid as Prescreener for the Earliest Alzheimer Pathological Changes

Abstract: ObjectiveWe investigated the association of plasma amyloid beta (Abeta)40, Abeta42, and total tau (tTau) with the presence of Alzheimer pathological changes in cognitively normal individuals with subjective cognitive decline (SCD).MethodsWe included 248 subjects with SCD (61 ± 9 years, 42% female, Mini‐Mental State Examination = 28 ± 2) from the SCIENCe project and Amsterdam Dementia Cohort. Subjects were dichotomized as amyloid abnormal by cerebrospinal fluid (CSF) and positron emission tomography (PET). Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
243
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 263 publications
(299 citation statements)
references
References 47 publications
(96 reference statements)
35
243
1
2
Order By: Relevance
“…In clinical studies focusing on Aβ‐PET–positive severe AD cases, both approaches revealed an accuracy of 85‐90% with the Aβ‐PET status. Most recently, Verberk et al [16] focused on the identification of cognitively normal individuals with subjective cognitive decline, which converted to MCI or AD over years, by measuring the A42/40 ratio in blood plasma using the Single Molecule Array technology. This approach resulted in the Amsterdam study in a diagnostic accuracy of 76% [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical studies focusing on Aβ‐PET–positive severe AD cases, both approaches revealed an accuracy of 85‐90% with the Aβ‐PET status. Most recently, Verberk et al [16] focused on the identification of cognitively normal individuals with subjective cognitive decline, which converted to MCI or AD over years, by measuring the A42/40 ratio in blood plasma using the Single Molecule Array technology. This approach resulted in the Amsterdam study in a diagnostic accuracy of 76% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Verberk et al [16] focused on the identification of cognitively normal individuals with subjective cognitive decline, which converted to MCI or AD over years, by measuring the A42/40 ratio in blood plasma using the Single Molecule Array technology. This approach resulted in the Amsterdam study in a diagnostic accuracy of 76% [16]. All technologies may be applied in combination to receive a powerful solely blood‐based AD recruitment platform.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Verberk et al showed that plasma Aβ42/Aβ40 ratio has potential to identify Alzheimer pathological changes in subjects with subjective memory decline . Furthermore, the inclusion of age and APOEε4 carriership in their multivariate model improved the likelihood of identification.…”
Section: Potential Conflicts Of Interestmentioning
confidence: 99%
“…We thank Prins et al for applying the methods of our article on “Plasma Amyloid as Prescreener for the Earliest Alzheimer Pathological Changes” to their research. Designing prescreening tools for amyloid positivity will ultimately facilitate recruitment of cognitively normal participants for Alzheimer disease clinical trials.…”
mentioning
confidence: 99%